2011
DOI: 10.1080/15226514.2011.573821
|View full text |Cite
|
Sign up to set email alerts
|

Reclamation of Highly Calcareous Saline Sodic Soil UsingAtriplex Halimusand by-Product Gypsum

Abstract: The removal of sodium salts from saline soils by salt tolerant crops, as alternative for costly chemical amendments, has emerged as an efficient low cost technology. Lysimeter experiments were carried out on a highly saline sodic soil (ECe = 65.3 dS m(-1), ESP = 27.4, CEC = 47.9 cmole+ kg(-1), and pH = 7.7) and irrigated with canal water (EC = 2.2 dSm(-1), SAR = 4.8) to investigate reclamation efficiency under four different treatments: control (no crop and no gypsum application) (C), gypsum application equiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(30 citation statements)
references
References 31 publications
8
22
0
Order By: Relevance
“…These results suggest that application of organic amendments can facilitate efficient replacement of Na + on the exchange sites by adding significant amounts of divalent cations and may further prevent the entry of Na + onto the exchange phase, when low SAR water is used as a leaching solution. Similar results of enhanced Na + leaching were observed in other studies when saline-sodic soils were treated with various amendments (Ahmad et al, 2006;Ghafoor et al, 2012;Gharaibeh et al, 2011;Jalali and Ranjbar, 2009). It should be noted that the cumulative amounts of cations given in mmolc column −1 (Figs.…”
Section: Leachate Ecsupporting
confidence: 77%
See 1 more Smart Citation
“…These results suggest that application of organic amendments can facilitate efficient replacement of Na + on the exchange sites by adding significant amounts of divalent cations and may further prevent the entry of Na + onto the exchange phase, when low SAR water is used as a leaching solution. Similar results of enhanced Na + leaching were observed in other studies when saline-sodic soils were treated with various amendments (Ahmad et al, 2006;Ghafoor et al, 2012;Gharaibeh et al, 2011;Jalali and Ranjbar, 2009). It should be noted that the cumulative amounts of cations given in mmolc column −1 (Figs.…”
Section: Leachate Ecsupporting
confidence: 77%
“…All treatments were effective in reducing the soil ESP to <15 after leaching with 7 pore volumes of reclaimed water including the control. Koo et al (1990) and Gharaibeh et al (2011) reported similar results with saline-sodic soil being reclaimed with irrigation water and attributed this effect to 'valence dilution' (Reeve and Doering, 1966), where adsorption of divalent cations is preferred at the expense of monovalent cations when soil solution is diluted by added water. ESP reductions were still significantly greater (P < 0.01) in soils amended with organic amendments than in the control soils (Fig.…”
Section: Soil Espsupporting
confidence: 61%
“…5), and nearly 30 species of landscape plants, including some salinity-sensitive species, were proposed with survival up to 90% after one or two years. Meanwhile, the approach is applicable to the field condition, which is very different from the traditional reclamation methods mainly used in soil columns, lysimeter experiments, laboratory experiments or greenhouse conditions (Ammari et al, 2013;Gharaibeh et al, 2011Gharaibeh et al, , 2009Hanay et al, 2004;Mahmoodabadi et al, 2013;Miranda et al, 2011;Nayak et al, 2008;Oster et al, 1999;Qadir et al, 1996;Sidhu et al, 2004;Siyal et al, 2010;Somani, 1981).…”
Section: Landscape Re-vegetationmentioning
confidence: 99%
“…Phytoremediation is a technology that can improve plantnutrient availability, extend the depth of the ameliorated zone, and may promote stability of soil aggregates and soil hydraulic properties (Gharaibeh et al, 2011;Qadir and Schubert, 2002). However, biological methods for utilization or vegetative bioremediation of salt-affected soils are limited by the growth environment and salinity tolerance of plants, and are usually combined with chemical amendments and/or leaching methods in reclamation of highly saline-sodic soils.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, in many arid environments, highquality water is not available to support the establishment of plants for revegetation projects. The removal of sodium salts from saline soils by tolerant plants, as an alternative for costly chemical amendments, has emerged as an efficient low-cost technology [9].…”
Section: Introductionmentioning
confidence: 99%